2014
DOI: 10.19173/irrodl.v15i5.1861
|View full text |Cite
|
Sign up to set email alerts
|

MOOC integration into secondary school courses

Abstract: We investigated how high school students taking a university preparatory economics course would engage with the learning and assessment components of a Behavioural Economics MOOC that was integrated into their school-based course. Students were divided into two groups, MOOC-only, with no teacher support, and blended-mode, with weekly tutorials. MOOC only students scored slightly lower on a teacher designed knowledge test but scored slightly higher in a MOOC test. Although the MOOC-only students watched more un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 6 publications
0
13
0
2
Order By: Relevance
“…The majority of current research and discussion related to MOOCs focuses on potential uses of MOOCs for (a) introducing high school students to college and higher education institutions (Horn, 2014;Najafi, Evans, & Federico, 2014), (b) using blended-learning approaches for current college students (Kolowich, 2013c), and (c) offering MOOCs for degree attainment or professional development (Stephens & Jones, 2014). This study revealed that another reason adult learners participate in MOOCs is to advance volunteerism and social justice efforts in order to engage in public knowledge building about controversial issues.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of current research and discussion related to MOOCs focuses on potential uses of MOOCs for (a) introducing high school students to college and higher education institutions (Horn, 2014;Najafi, Evans, & Federico, 2014), (b) using blended-learning approaches for current college students (Kolowich, 2013c), and (c) offering MOOCs for degree attainment or professional development (Stephens & Jones, 2014). This study revealed that another reason adult learners participate in MOOCs is to advance volunteerism and social justice efforts in order to engage in public knowledge building about controversial issues.…”
Section: Discussionmentioning
confidence: 99%
“…Their method acknowledges micro learning, which is lacking in those other methods that only measure rates of completion. Najafi et al (2014) found that learners engaged with assessment and learning elements of an integrated online course in a manner that was highly dependent on self-study. They argued that their results are promising, especially when it comes to incorporating MOOCs in a self-study method in school-based programs.…”
Section: Resultsmentioning
confidence: 99%
“…These are considered the second most interesting type of research for the scholars to explore students' views and instructors' views toward the use of MOOCs (e.g. Najafi et al, 2014;Bruff et al, 2013;Loizzo, 2015;Patil et al, 2016;Dal Magro et al, 2017;Eriksson et al, 2017;Leach & Hadi, 2017;Firmansyah & Timmis, 2016;Salvador & Rodriguez-Hoyos, 2016;Linna et al, 2016).…”
Section: Discussion and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 2 the list of the platforms that are referred in more than four articles is presented, as well as the references of the articles themselves. [Canessa et al 2013], [Fox, 2013], [Monedero-Moya et al 2015], [Moodie 2014], [Najafi et al 2014] and [Reilly et al 2014][Comer et al 2014], [Fisher 2014], [Fowler and Smith 2013], [Jiang et al 2014…”
Section: Identification Of Moocs Platformsmentioning
confidence: 99%